2020
DOI: 10.1371/journal.pone.0242926
|View full text |Cite|
|
Sign up to set email alerts
|

Protein fractional synthesis rates within tissues of high- and low-active mice

Abstract: With the rise in physical inactivity and its related diseases, it is necessary to understand the mechanisms involved in physical activity regulation. Biological factors regulating physical activity are studied to establish a possible target for improving the physical activity level. However, little is known about the role metabolism plays in physical activity regulation. Therefore, we studied protein fractional synthesis rate (FSR) of multiple organ tissues of 12-week-old male mice that were previously establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Gentry et al (2002) showed no differences in the percentage of muscle fibre types when pigs were reared in long pens with 10 times more space allowance, even though they noticed higher physical activity than those reared in conventional dimensions. Similarly, neither Cross et al (2020) found differences between inherently low‐active and high‐active inbred strain mice; while low‐active mice had a higher kidney FSR. In addition to increased physical activity, access to the outdoors may lead to greater exposure to temperature fluctuations.…”
Section: Factors Influencing Protein Turnover Ratesmentioning
confidence: 88%
See 2 more Smart Citations
“…Gentry et al (2002) showed no differences in the percentage of muscle fibre types when pigs were reared in long pens with 10 times more space allowance, even though they noticed higher physical activity than those reared in conventional dimensions. Similarly, neither Cross et al (2020) found differences between inherently low‐active and high‐active inbred strain mice; while low‐active mice had a higher kidney FSR. In addition to increased physical activity, access to the outdoors may lead to greater exposure to temperature fluctuations.…”
Section: Factors Influencing Protein Turnover Ratesmentioning
confidence: 88%
“…The mechanisms responsible for protein turnover vary for each type of protein, resulting in differences among organs and tissues. There is wide evidence that skeletal musculature has a relatively slow turnover rate in comparison with several visceral organs (Bregendahl et al, 2008; Cross et al, 2020; Garlick et al, 1976; Ten Have et al, 2019). According to Garlick et al (1976), protein FSR of skeletal muscle are 77–86% lower than those of spleen, kidney, liver and lungs, and 47% lower than those of the brain.…”
Section: Factors Influencing Protein Turnover Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Future murine studies should expand this number to include both males and females of inbred (e.g., CD2F1), and outbred strains (e.g., CD-1), due to their reported differences in radiation sensitivity (75). Additionally, while C3H/HeJ, BALB/c, and C57BL/6 have been reported to exhibit differences in their DNA repair pathways, immune response, protein synthesis rates, and hemostatic conditions (76)(77)(78)(79), studying the effect of each of these factors individually on the miRNA expression could greatly improve our understanding of the RNA response to radiation. Furthermore, although they are beneficial for initial studies, mouse models are inherently limited by their limited translatability to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Calculations. Based on previous work (22), we chose to analyze the true precursor of the incorporation into protein alanine rather than an indirect measurement. We calculated the labeled to unlabeled ratio (tracer-tracee ratio (TTR)) of alanine of each organ tissue and corrected the value with the natural abundance of the tracer.…”
Section: Methodsmentioning
confidence: 99%